2017
DOI: 10.1101/132563
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Translating GWAS Findings Into Therapies For Depression And Anxiety Disorders: Drug Repositioning Using Gene-Set Analyses Reveals Enrichment Of Psychiatric Drug Classes

Abstract: Depression and anxiety disorders are the first and sixth leading cause of disability worldwide according to latest reports from the World Health Organization. Despite their high prevalence and the significant disability resulted, there are limited advances in new drug development. On the other hand, the advent of genome-wide association studies (GWAS) has greatly improved our understanding of the genetic basis underlying psychiatric disorders.In this work we employed gene-set analyses of GWAS summary statistic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2017
2017
2019
2019

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 110 publications
0
2
1
Order By: Relevance
“…The current results do not provide sufficient evidence for the 410 association of these drugs and their effects on the PF-ranked genes found for PD; in fact, no gene-411 drug association was found either at the individual drug level, or at the drug class level. Differently 412 from previous reports (So, 2017;So et al, 2016), which support drug repositioning from genes 413 extracted from GWAS for anxiety and mood disorders, our findings do not support such proposals. 414 Extensive methodological differences are probably responsible for this discrepancy.…”
Section: Drug Repositioning Attempts 405contrasting
confidence: 99%
“…The current results do not provide sufficient evidence for the 410 association of these drugs and their effects on the PF-ranked genes found for PD; in fact, no gene-411 drug association was found either at the individual drug level, or at the drug class level. Differently 412 from previous reports (So, 2017;So et al, 2016), which support drug repositioning from genes 413 extracted from GWAS for anxiety and mood disorders, our findings do not support such proposals. 414 Extensive methodological differences are probably responsible for this discrepancy.…”
Section: Drug Repositioning Attempts 405contrasting
confidence: 99%
“…The enrichment of calcium channels confirms that calcium channel blockers such as verapamil may provide repurposing opportunities for MDD, 26 although their effects on blood pressure may prove problematic. 27 Pregabalin and gabapentin, both calcium channel modulators, are also top ranked repurposing candidates. Pregabalin has been shown to be an effective adjunctive treatment for MDD 28 and treatment-resistant bipolar disorder, 29 and gabapentin is used off-label for bipolar disorder.…”
Section: Discussionmentioning
confidence: 99%
“…Another study by Gasper et al 55 reported that as sample size increases, SCZ GWAS results were increasingly enriched for known psychiatric medications. We also recently revealed that GWAS results of depression and anxiety disorders (and related phenotypes) were enriched for psychiatric drug classes including antidepressants 56 . Taken together, the current study adds to the mounting evidence that data from human genomic studies are useful in guiding drug development in neuropsychiatry.…”
Section: Discussionmentioning
confidence: 99%